Edukasi Bounding Attachment dalam Upaya Menciptakan Hubungan Ibu dan Anak setelah Melahirkan - Dewi Susilawati; Nur Fadjri Nilakesuma; Novria Hesti; Yeni Gea; Nur Salsabila W S; Ramadhany Hafsah Qonita; Armein Syahid (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The Indonesian Demographic and Health Survey results in 2017 showed that the MMR was 305/100,000 births and the IMR in Indonesia was 24/100,000 live births. One way to overcome MMR and IMR is to implement bounding attachments. There are various ways to do bounding attachments, including Early Initiation of Breastfeeding and exclusive breastfeeding. The achievement of Exclusive Breastfeeding in the Working Area of ​​the Air Cold Health Center is 66.5%, still far from the government's target of 80%. Independent Practice Midwife Silvia Nova Sari is one of the PMBs in the working area of ​​the Air Cold Health Center, Balai Gadang Village, Koto Tangah District, Padang City. Based on interviews with breastfeeding mothers at PMB Silvia Nova Sari, it was found that most mothers did not know about bounding attachments and how to create them. Likewise with PMB owners, that as health workers, not all mothers get bounding attachment education to pregnant women. Activities carried out include health promotion by providing information and education to pregnant women and their families with a Focus Group Discussion approach on creating bounding attachments between mothers and babies, which was held on 30 September-1 October 2020. Each stage was attended by five pregnant women with due observance of health protocols. The result of bounding attachment education for pregnant women is that almost all mothers experience an increase in knowledge about bounding attachment, seen from the questionnaire results given before and after education.